2005
DOI: 10.1179/016164105x35495
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular reconstruction by means of stent placement in symptomatic intracranial atherosclerotic stenosis

Abstract: In selected patients, endovascular revascularization of intracranial arteries by means of stent-assisted angioplasty is technically feasible, effective and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…Marks et al 43 reported a much higher rate of significant postoperative residual stenosis in intracranial angioplasty series (18/36 cases, 50%). In contrast, Lylyk el al 44 found no significant postoperative residual stenosis in 104 intracranial stenting procedures. Our data suggest that the rates of periprocedural stroke and death were similar in both groups.…”
Section: Siddiq Et Al Angioplasty Vs Stenting For Intracranial Atheromentioning
confidence: 97%
“…Marks et al 43 reported a much higher rate of significant postoperative residual stenosis in intracranial angioplasty series (18/36 cases, 50%). In contrast, Lylyk el al 44 found no significant postoperative residual stenosis in 104 intracranial stenting procedures. Our data suggest that the rates of periprocedural stroke and death were similar in both groups.…”
Section: Siddiq Et Al Angioplasty Vs Stenting For Intracranial Atheromentioning
confidence: 97%
“…In our series there was also one 79-year-old female patient with a fateful course of vessel rupture. Recently, the advent of a new generation of more flexible stents has prompted consideration of stent-assisted angioplasty as an alternative approach for treatment of intracranial stenosis [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…This finding led the authors to conclude that any benefit from stenting was observed primarily in the group with severe stenosis given that, based on WASID, significantly more recurrent events would have been expected in the severe stenosis group. A smaller prospective single-center study from Argentina (104 patients) reported a 5.7% procedural morbidity rate, including a 3.8% risk of death [31].…”
Section: Large Case Seriesmentioning
confidence: 99%